Experimental determination of invasive fitness in Caenorhabditis elegans - Chelo, Ivo M (2017)
The deposited article is a post-print version and has been submitted to peer reviewing. This publication hasn't any creative commons license associated. The deposited article version contains attached some supplementary materials within the pdf. Some supplementary materials are not present in the uploaded version of the article, are present in the publisher's page in the following link: https://www.nature.com/articles/nprot.2014.098#integrated-supplementary-information